Thirteen new weeds on Cedros Island, Baja California, Mexico - Vanderplank, Sula E; Rebman, Jon (Instituto de Ecología, A.C., 2021)
Background and Aims: Cedros Island is the southernmost outpost of the California Floristic Province, the largest island in the Californian archipelago, and home to a suite of endemic plants and animals. As such, it is an important resource within the Pacific Islands Biosphere Reserve, with many management concerns. The goal of this study was to document newly arrived plant species on Cedros Island, Baja California, Mexico.Methods: From the 8th to the 11th February 2019 we visited Cedros Island and made observations of plants around Cedros Village using the platform NaturaLista (iNaturalist).Key results: Thirteen new plant taxa were detected around Cedros village, all were non-native. These discoveries follow a very recently published checklist on the flora and suggest that new non-native plants are arriving rapidly. Conclusions: Recommended management implications include monitoring and eradication of new species, particularly at inhabited areas, and with priority given to highly invasive species such as Cenchrus setaceus and C. ciliaris.